The Pol Pot regime : race, power, and genocide in Cambodia under the Khmer Rouge, 1975-79 - Kiernan, Ben (Yale University Press, 1996)
The Khmer Rouge revolution turned Cambodia into grisly killing fields, as the Pol Pot regime murdered or starved to death a million and a half of Cambodia's eight million inhabitants. This book - the first comprehensive study of the Pol Pot regime - describes the violent origins, social context, and course of the revolution, providing a new answer to the question of why a group of Cambodian intellectuals imposed genocide on their own country.
Keywords: Parti communiste du Kampuchea.; Parti communiste du Kampuchea; Pol Pot -- 1928-1998; Rote Khmer; Pol Pot.; Cambodia -- Politics and government -- 1975-1979.; Communism -- Cambodia.; Political atrocities -- Cambodia.; Genocide -- Cambodia.; Cambodge -- Politique et gouvernement -- 1975-1979.; Atrocités politiques -- Cambodge.; HISTORY.; Communism; Genocide; Political atrocities; Politics and government; Cambodia; Kommunismus; Politik; Völkermord; Kambodscha.; Rode Khmer.; Revoluties.; Massamoorden.; 1975-1979